IDENTIFICATION AND MAPPING OF DOMESTIC WATER SUPPLY SOURCES IN GYEL DISTRICT OF JOS, PLATEAU STATE, NIGERIA - OMADA1, MESHACH AROME; ALI, ANDESIKUTEB YAKUBU; EZRA LEKWOT , VIVAN; GIWA, CLEMENT YAKUBU; HYACINTMADAKIDALOENG; IGUISI, EDWIN OSAWE (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
The challenges of public water supply in most cities and suburban areas of developing countries are increasing with increase in population, poor operational efficiency of existing waterworks and infrastructure, leakages, low reticulation coverage, poor service delivery and poor cost-recovery. The study is aimed to identify and map the public water supply sources in Gyel District of Jos South Local Government of Plateau State, Nigeria. The study adopted the use of Satellite data, coordinates of various sources of domestic water and their attributes, population data coupled with a structured questionnaire and photographs from field in achieving the objectives of identifying and mapping of water supply sources in the area. Spatial analytical method such as; Density and Proximity analysis were used to identify the water sources with the aid of ArcGIS 10.3 tool in Mapping and Geo-processing, while SPSS and Microsoft software were used for computing the statistical analysis. Thus, the result obtained was; Hand dug well has the highest frequency of coordinates among the public water sources like public bore holes and pipe borne water, in which 60% of the respondents used it as their primary source of domestic water supply. The pattern of the distribution of water supply facilities were found clustered around the city centre and well planned cadastral area, this exert serious pressure on access to the sources especially on those within the unplanned and newly developed area as only 32% of the respondents have access to the public domestic water sources. Most of the built-up areas which constituted the households fall within the basic access and No-access level where the standards for domestic water usage are not met. Therefore, the following recommendations were suggested, which are; Encouragement for the provision of more domestic water sources by the Plateau State Water Board (PSWB), The Jos metropolitan Development Board (JMDB) should ensure built-up areas adopt town planning standard and the PSWB should ensure periodic extension service of water supply facilities in the area.